If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -6x = -66 Solving 12 + -6x = -66 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -6x = -66 + -12 Combine like terms: 12 + -12 = 0 0 + -6x = -66 + -12 -6x = -66 + -12 Combine like terms: -66 + -12 = -78 -6x = -78 Divide each side by '-6'. x = 13 Simplifying x = 13
| (5x+6)-(-2x^2-7x+6)=0 | | 5r-4r+(-4r)-18r-(-19r)=-8 | | 9p-13=17+4p | | 7/10p=-14/13 | | 3(-1)+y=14 | | 3(0)+y=14 | | 0.95=2.5g+0.45 | | 29-8x=-7(x-5) | | 6x=-26/4 | | 27/30 | | 16r-(-19r)+(-14r)-19r=-20 | | (3x+6)*(x+1)=18x | | 2.3z=4.6 | | 30/42 | | R-13=15 | | 2m+4=2m-4 | | 31=-(1+6p)+4(p+6) | | log(7/(x^2)-9) | | -4y+5=-8y | | 80=-45+x | | 11d-10d-d+4d+3d+2=16 | | 4+8x=9x-8 | | sin(1.5)=(5/x) | | -5y=-15x+40 | | F-14=3f+18+2f | | x-4=1/2x | | 2(n-2)=n-16+5n | | 3/5t=30 | | 2y=4x-22 | | 16g-g+3g-17g=11 | | 5x+9=7x+-135 | | 3x^2-15xy-5x+25y= |